Improvement Of Free Space Optical Communications Using Double Carrier Modulation/Differential Detection - Hitam, Salasiah (2006)

(untitled)
Free Space Optical (FSO) communications receive growing attention for use in high data rates wireless link with recent commercialization successes. It is an interesting solution to achieve high bandwidth in the ‘last-mile’ problem with economical and fast deployment. However, in the poor weather such as the heavy rainfall and low visibility lead to degradation of the links performance, particularly over ranges of several hundred meters or longer. Rare usage of FSO communications might be related to factors which are classified as scintillation, absorption, and scattering. In this purpose of studies, the heavy rainfall and low visibility data in Subang Airport, Malaysia were used for the analysis on conventional technique that is Intensity Modulation/Direct Detection (IM/DD) and a new technique namely Double Carrier Modulation/Differential Detection (DCM/Diff.D) as the worst case scenario.Currently, most FSO communication systems are using the IM/DD which are still subjected to many problems. The main problems associated with FSO transmission systems are; atmospheric loss, geometric loss, mispointing loss, and the inability of the receiver circuit to regenerate the transmitted bits because of low signal power. Another prevalent problem is that of its masking noises. The recovery technique in the IM/DD technique uses an injected voltage level as a threshold into a decision circuit, which decides whether the incoming bit is a ‘0’ or a ‘1’. This technique has two inherent problems; the instability of the injected threshold voltage, and the complexity of a dynamic threshold processing. Due to these problems, a new technique based on the automatic decision making known as DCM/Diff.D is provided to improve the transmissions. The performance of IM/DD and DCM/Diff.D was simulated by using commercial simulation software, OptiSystem Version 3.1 and 4. From the simulation results, it appears clearly that the DCM/Diff.D technique improves for more than twice the distance supported by the IM/DD technique under the conditions of heavy rainfall and hazy days. The theoretical development on probability of error and digital signal-to-noise ratio for the worst case scenario also support these results. Another outcome in this thesis is the theoretical derivation on positioning a passive reflector with a time delay produced can be acceptable until 2.5 Gbps.